2005
DOI: 10.1186/1472-698x-5-4
|View full text |Cite
|
Sign up to set email alerts
|

Good governance and good health: The role of societal structures in the human immunodeficiency virus pandemic

Abstract: BackgroundOnly governments sensitive to the demands of their citizens appropriately respond to needs of their nation. Based on Professor Amartya Sen's analysis of the link between famine and democracy, the following null hypothesis was tested: "Human Immunodeficiency Virus (HIV) prevalence is not associated with governance".MethodsGovernance has been divided by a recent World Bank paper into six dimensions. These include Voice and Accountability, Political Stability and Absence of Violence, Government Effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 6 publications
1
22
0
Order By: Relevance
“…Menon-Johansson 54 has shown that HIV prevalence is higher in countries with poor governance. The UN Commission on HIV/AIDS and Governance in Africa is an example of the growing importance of prioritizing institutional design and rule of law in fostering sustained outcomes from HIV interventions; including ART scale-up.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Menon-Johansson 54 has shown that HIV prevalence is higher in countries with poor governance. The UN Commission on HIV/AIDS and Governance in Africa is an example of the growing importance of prioritizing institutional design and rule of law in fostering sustained outcomes from HIV interventions; including ART scale-up.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…I would like to thank Drs Reidpath and Allotey for their analysis [1] of some of the variables described in the tables of the initial paper [2] and their use of other health and economic data to demonstrate correlations with governance.…”
Section: Textmentioning
confidence: 99%
“…The small GDP-PPP in low governance countries is compounded by poorer distribution of wealth. The impact of GDP-PPP on life expectancy in 2002 is demonstrated in Figure 1, using data from the additional file included with the original paper [2]. In poor countries, small increases in wealth produce a dramatic increase in life expectancy with diminishing returns above the median life expectancy of 69.4 years in 2002.…”
Section: Textmentioning
confidence: 99%
“…Several other primary articles, which are not even related to the research questions, were also included. These are, for example, studies on sub‐Saharan infant mortality (Fayissa, ), on HIV prevalence in 149 nations (Menon‐Johansson, ), and on new welfare state typology, factoring in healthcare factors (Bambra, ). Other debatable articles are on mental health (Nordenmark, Strandh, & Layte, ), reviewed by both the Muntaner group and the Brennenstuhl group; on happiness (Deeming & Hayes, ) included by the Bergqvist group; or on oral health (Sanders et al, ) reviewed by the Bregqvist group again.…”
Section: Resultsmentioning
confidence: 99%